Mixed methods procedures and designs for research on sport, physical education and dance - Arguera, M. T.; Camerino, O.; Castaner, M. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
In this book we aim to show that quantitative and qualitative methods can be integrated and complement one another through what is generally known as the mixed methods approach, sometimes referred to as synthetic interpretative methodology or qualiquantology. Whatever the term used, the process involves the collection, analysis and combination of quantitative and qualitative data in the same study. Some authors have likened the emergence of this approach to a 'silent revolution'. At all events, the notion of mixed methods refers not merely to the gathering of different kinds of data about the same behaviour or episode, but also implies combining the inductive approach to concept generation with deductive logic. Furthermore, the mixing applies to the whole research process, i.e. problem definition, data collection, data analysis, interpretation of results, and the final report. Authors believe that such an approach can offer a more holistic understanding of human motor behaviour and is well suited to dealing with its complexity. Although it has only recently begun to be applied in research on physical activity and sport, the broad potential of mixed methods is illustrated by the increasing number of related publications in this field.